2018
DOI: 10.1111/jace.15558
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐IR transparent TeO2‐TiO2‐La2O3 glass and its crystallization behavior for photonic applications

Abstract: In this report, effect of enhanced rare earth (La2O3) concentration on substitution of TeO2 within ternary TeO2‐TiO2‐La2O3 (TTL) glass system has been studied with respect to its thermal, structural, mechanical, optical, and crystallization properties with an aim to achieve glass and glass‐ceramics having rare‐earth‐rich crystalline phase for nonlinear optical and infrared photonic applications. DSC analysis (10°C/min) demonstrates a progressive increase in glass‐transition temperature (Tg) from 359 to 452°C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Figure shows the differential scanning calorimetric (DSC) curves at a heating rate ( β ) of 10 K min −1 of TTLG, TTLGH1, and TTLGH2 glass samples. Characteristic temperatures such as glass transition region ( T g ), onset crystallization temperature ( T x ), and peak crystallization temperature ( T p ) obtained from DSC thermographs are shown in Table . For the present series of glass, the value of T g is around 430 °C, whereas the value of T x ranges from 470 to 472 °C.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Figure shows the differential scanning calorimetric (DSC) curves at a heating rate ( β ) of 10 K min −1 of TTLG, TTLGH1, and TTLGH2 glass samples. Characteristic temperatures such as glass transition region ( T g ), onset crystallization temperature ( T x ), and peak crystallization temperature ( T p ) obtained from DSC thermographs are shown in Table . For the present series of glass, the value of T g is around 430 °C, whereas the value of T x ranges from 470 to 472 °C.…”
Section: Resultsmentioning
confidence: 88%
“…In general, an increase in the concentration of modifier components in the tellurite glass composition increases the conversion of TeO 4 structural units into TeO 3 /TeO 3+1 units containing NBOs that are coordinated to the modifier cations . In an earlier effort, authors identified the role of La 2 O 3 as a network modifier in the titanium tellurite glass (i.e., TTL10: 80TeO 2 –10TiO 2 –10La 2 O 3 ) from the variation in the intensity of high‐frequency Raman shift regions resulted due to the depolymerisation of the network structure through the formation of TeO 3 and TeO 3+1 units over TeO 4 units . The comparison of Raman spectrum of TTLG glass with the TTL10 glass (Figure S‐VI(c), Supporting Information) reveals that the Gd 3+ ions also play the similar role of La 3+ ions in the network of TTLG glass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The peak crystallization temperature T p increases from 950 ℃ to 967 ℃ when the heating rate increases from 5 ℃⋅ min − 1 to 40 ℃⋅ min − 1 . The peak crystallization temperature and corresponding heating rate are used to estimate the crystallization activation energy E a through established models such as Kissinger, Augis-Bennett, and Ozawa models [32,33].…”
Section: Crystallization Kinetics Analysis Of Ay26 Glassmentioning
confidence: 99%